Involvement of heat shock proteins HSP70 in the mechanisms of endogenous neuroprotection: the prospect of using HSP70 modulators - Belenichev, Igor F.; Aliyeva, Olena G.; Popazova, Olena O.; Bukhtiyarova, Nina V. (Frontiers in Cellular Neuroscience, 2023)
This analytical review summarizes literature data and our own research on HSP70-dependent mechanisms of neuroprotection and discusses potential pharmacological agents that can influence HSP70 expression to improve neurological outcomes and effective therapy. The authors formed a systemic concepts of the role of HSP70-dependent mechanisms of endogenous neuroprotection aimed at stopping the formation of mitochondrial dysfunction, activation of apoptosis, desensitization of estrogen receptors, reduction of oxidative and nitrosative stress, prevention of morphofunctional changes in brain cells during cerebral ischemia, and experimentally substantiated new target links for neuroprotection. Heat shock proteins (HSPs) are an evolutionarily integral part of the functioning of all cells acting as intracellular chaperones that support cell proteostasis under normal and various stress conditions (hyperthermia, hypoxia, oxidative stress, radiation, etc.). The greatest curiosity in conditions of ischemic brain damage is the HSP70 protein, as an important component of the endogenous neuroprotection system, which, first of all, performs the function of intracellular chaperones and ensures the processes of folding, holding and transport of synthesized proteins, as well as their degradation, both under normoxic conditions and and stress-induced denaturation. In response to the cerebral ischemia formation, HIF-1a is expressed, which initiates the launch of compensatory mechanisms for energy production and HSP70 "prolongs" the action of HIF-1a. During ischemia of organs and tissues, HSP70 performs a protective function, which is realized through increased synthesis of antioxidant enzymes, stabilization of oxidatively damaged macromolecules, and direct anti-apoptotic and mitoprotective action. Such a role of these proteins in cellular reactions during ischemia raises the question of the development of new neuroprotective agents which are able to provide modulation/protection of the genes encoding the synthesis of HSP 70 and HIF-1a proteins. Numerous studies of recent years have noted the important role of HSP70 in the implementation of the mechanisms of metabolic adaptation, neuroplasticity and neuroprotection of brain cells, so the positive modulation of the HSP70 system is a perspective concept of neuroprotection, which can improve the efficiency of the treatment of ischemic-hypoxic brain damage and be the basis for substantiating of the feasibility of using of HSP70 modulators as promising neuroprotectors.